Early Career South African Occupational Therapists’ Perceptions of Person–Environment Fit in Work–Life Areas That Influence Work Stress - Patricia de Witt; Morgann Bruce; Marica Botha; Denise Franzsen (Occupational Therapy International)
Conclusion: Workload impacted workplace-related stress in respondents with scores below the norm on the AWS for this work–life area. Although some work-related factors affected workplace-related stress, the overall scores for the other work–life areas were above the norm, with only respondents in public service settings and in the field of physical rehabilitation reporting low work environment fit.